Cash Waqf Linked Sukuk (CWLS) for Sustainable Social Infrastructure Financing: Integrating Islamic Social Finance, Maqasid al-Shariah, and Sustainable Development - Taufik Kurrohman; Lukman Hakim (Lembaga Bale Literasi, 2026)
The development of Islamic social finance has stimulated the emergence of innovative financial instruments aimed at supporting sustainable social development. One of the most prominent innovations is Cash Waqf Linked Sukuk (CWLS), a hybrid instrument that integrates cash waqf with sovereign sukuk through a Shar??ah-compliant and productive financing mechanism. This study examines the conceptual framework of CWLS within the broader context of Islamic finance, analyzes its operational mechanism in financing social infrastructure, and proposes strategies to strengthen its role in sustainable development. Employing a normative legal research design, the study adopts conceptual, statutory, and Islamic economics approaches. Data were collected through an extensive literature review of laws and regulations, fatwas issued by the National Shar??ah Council of the Indonesian Council of Ulama (DSN-MUI), scholarly publications, Islamic economics literature, and reports from Islamic financial institutions. The data were analyzed using content analysis, comparative analysis, and normative legal analysis. The findings reveal that CWLS effectively integrates philanthropic and investment functions within a secure and sustainable financial framework. By preserving the principal value of waqf assets while channeling investment returns from sovereign sukuk to social programs, CWLS generates sustainable financing for education, healthcare, poverty alleviation, and community economic empowerment. Furthermore, the instrument demonstrates strong alignment with the objectives of Maq??id al-Shar??ah, Sustainable Development Goals (SDGs), and the broader agenda of sustainable Islamic finance. The study argues that optimizing the developmental impact of CWLS requires regulatory harmonization, enhanced institutional capacity of nazir, improved public literacy, and accelerated digital transformation of waqf governance. The novelty of this study lies in its integration of productive waqf theory, social infrastructure financing, sustainable Islamic finance, and Maq??id al-Shar??ah within a comprehensive analytical framework for assessing CWLS as a sustainable development instrument.